Research trends in brain imaging of mild cognitive impairment in 25 years: a bibliometric analysis - Daniella Satyasari; Agnes Tineke Waney Rorong (Faculty of Medicine, Universitas Trisakti, 2023)
Mild cognitive impairment (MCI) is a condition that is experienced by most elderly in the world. Although there has been a huge rise in research on developing brain imaging tests that can identify and evaluate MCI early on, a bibliometric analysis of this issue is still lacking. The purpose of this review is to determine the pattern and growth of research trends related to MCI and brain imaging using bibliometric analysis, based on Scopus data from 1996 to 2021. The data was converted to Comma Separated Values (CSV) and exported to VOSviewer to bibliometrically analyze the origin by country, keywords, frequently cited articles, author, and journals. Over a 25-year period, 5081 articles were discovered, with the number rising, particularly in the past four years, and significantly in 2022 when 561 articles (11.04%) were found. The Journal of Alzheimer's Disease (19.22%) and Neuroimage Clinical (10.22%) published the largest number of articles on this subject. The United States (24.31%) led all other countries in the number of publications, followed by China (14.84%) and UK (6.5%). The most cited article was by Petersen RC in 1999 (41 citations) about MCI and its clinical characterization. The keywords that appeared the most frequently were mild cognitive impairment (984 occurrences) associated with biomarkers, brain scanning procedures, brain part, age, and human subject. The most frequently cited authors were Petersen RC (1365 citations) and Jack CR (1103 citations). Neuroimage (4164 citations), and Neurology (3268 citations) are the most repeatedly cited journals. This bibliometric study displays the trend in the last 25 years for MCI and brain imaging.